FREE PARKING FOR ALL IN SHOPPING MALLS. (November 2014) - Hasker, Kevin; Inci, Eren
Abstract : We show why a mall provides parking for free and embed the parking costs in the prices of the goods. Essentially, charging a parking fee to risk‐averse customers means penalizing them for not finding their desired good. This result holds whether the mall has monopoly power or prices competitively, if there is parking validation, and if there is a trade‐off between shopping and parking spaces. It is also the attainable social optimum. The equilibrium lot size is too small, yielding a rationale for minimum parking requirements. However, parking fees may be positive and lots may be too large in urban malls.